Pendampingan Aset Ekonomi Anggota PKK Melalui Tata Boga - Kholik, Kusnul (Janaka, Jurnal Pengabdian Masyarakat, 2019)
Community economic empowerment is suspected to be effective if based on the empowerment of individual potential and assets. Such efforts are implemented in Kedunggalih Gondang Nganjuk, economic assets in the form of processed agricultural products and individual assets in the form of lots of free time owned by PKK members are opportunities to be more empowered. This economic empowerment uses the Asset-based Community Development (ABCD) approach. Researchers collaborated with agents from the village apparatus and Posyandu cadres to mobilize PKK members to be involved in catering. The results obtained from this training were to increase the awareness of mothers to increase the variety of processed foods to be marketed in their own internal environment. The supporting factor for the success of the activity is the involvement of agents of change that come from village officials and Posyandu cadres in solving problems faced by residents. The change agents are considered to be able to carry out the function of a catalyst in an effort to achieve economic business improvement